Analisis Natrium Siklamat Dalam Minuman Tebu(Saccharum Officinarum, L) Secara Spektrofotometri - Lidyawati Lidyawati; Rosa Mardiana; Dwi Putri Rejeki; Jauhari Jauhari (Forum Kerjasama Pendidikan Tinggi (FKPT), 2020)
Sodium Cyclamate is one type of sweetener that is permitted, although being allowed to use excess sodium cyclamate can lead to cancer formation. Long-term consumption of sodium cyclamate can lead to metabolism of sodium cyclamate into cyclohexilamine compounds. The purpose of this study was to determine how much sodium cyclamate is used, whether it exceeds the maximum limit of 500 mg / kg weight of the material that has been determined. The sample used was a sample of sugarcane juice sold in Darussalam, which was then examined at the Chemical Laboratory of UIN Ar-raniry and FKIP Kimia Unsyiah Banda Aceh. The analytical method used is quantitative analysis using the UV-vis spectrophotometry method to determine the sodium cyclamate level. The results showed that the 4 samples used were negative containing sodium cyclamate with the level of Sample I = -449.8 Sample 2 = -426.4 Sample 3 = -520.6 Sample 4 = -444.8.